A framework for subcontractor selection in the construction industry - Abbasianjahromi, Hamidreza; Rajaie, Hossein; Shakeri, Eqbal (Journal of Civil Engineering and Management, 2013)
The present condition of the construction industry imposes onerous responsibilities on contractors so they are very eager to subcontract some of their works. Subcontractors who directly handle a major portion of all construction activities have a highlighted role in the building industry, so suitable subcontractor selection has a direct effect on the productivity of construction operations. This paper aims to develop a comprehensive model for subcontractor selection based on the fuzzy preference selection index. The improvement of the proposed model lies in the fact that it has found a way to eliminate the weighting criteria phase in selecting the optimal subcontractor where weighting attributes is a challenging task. The consistency test is presented for investigating the accuracy of model results with the previous scientific work.